Implementation of internal control and utilization of accounting information systems on the financial quality of PT. Misool Eco Resort (Case study in South Misol Islands, Raja Ampat Regency) - Wermasubun, Ruth Octaviani P.; Kalangi, Linjte; Wokas, Heince R. N. (Yayasan Widyantara Nawasena Raharja, 2025)
This study examines the implementation of internal control and the use of accounting information systems on the financial reporting quality of PT. Misool Eco Resort. Using a qualitative case study approach, data were collected through interviews, observations, and document analysis. Key informants included the administrative director, operational manager, financial manager, accounting supervisor, and controller. The findings indicate that the internal control system is inadequate, with suboptimal results across the eight components of the control environment. Weaknesses include insufficient enforcement of integrity and ethical values, unclear delegation of authority and responsibility, and an ineffective controller role in ensuring compliance and goal achievement. The accounting information system, utilizing the Mekari Jurnal application, performs well in terms of speed, usability, and information quality. However, issues such as data synchronization between branches and headquarters remain. Although the accounting system contributes positively to financial reporting, weaknesses in internal control compromise the reliability and accuracy of financial statements. The study recommends enhancing internal control through improved communication of ethical standards, employee competency development, organizational restructuring, and strengthening the controller’s role. Greater integration between internal control and the accounting system is essential to ensure the production of high-quality financial reports in compliance with financial accounting standards.